Music as a blend of spirituality, culture, and mind mollifying drug. (28th February 2022) - Arora, Shefali; Tyagi, Abhinav
Highlights: Music is a spiritual expression of universal nature. Music therapy has the power to heal various diseases and enhance the immune system. Spotify is the easiest way to inject music into a user's self-care especially during COVID-19 period. Global wellness Music:A new technology captures the user's biometric data for personlized healing. Ethnomusicology contains detailed analysis that explains the interaction and unique relationship among music, culture, and society. Abstract: Science inspires music more often than human imagination. Music is an integral part of all societies, including animal ones. It is behaving like an instrument for digesting information. It has been proven to help in healing the body, mind, and culture. Music can maintain and regulate emotion. It is a common thread among large social groups and is used as a tool to navigate through life. Real science and real music require a steady thinking process. It is a way of finding compatibility within a society as well as developing a link with other societies. Music plays a developmental role in a person's identity, cultural worldview and permeates through life. In nutshell "Science explains Music and Music makes us The Human"